The use of scenarios in legal education to develop futures thinking and sustainability competencies. Issue 3 (1st September 2016) - Lim, Michelle; Allan, Andrew
Abstract : Achieving sustainability requires a populace equipped to deal with complex, interacting and ever-changing realities as well as uncertain futures. There is however a significant lack of focus on developing sustainability competencies within legal and governance education. Legal education plays a key role in shaping sustainable futures. Long-term sustainability relies on lawyers, judges and policy-makers being able to make optimal decisions in the present when faced with significant uncertainty about the future. This paper discusses how the combination of problem-based learning (PBL) and scenario-based pedagogical approaches can provide an authentic contextualised learning environment to empower law students to deal with the challenges of global change. The paper highlights the potential of the approach to equip students with the skills to work through plausible future challenges; to consider a range of options; and to manage interacting environmental, social and economic issues in an adaptive fashion. The paper describes how the approach was applied in the context of the Water Law Master's (LLM) course at the University of Dundee. The paper concludes with recommendations of how scenario-based approaches could be used in other contexts and further highlights the importance of such approaches in developing sustainability competencies through the legal curriculum.